ASSESSMENT OF FACTORS INFLUENCING THE CONSUMPTION OF LOCAL DRINKS IN RURAL OSUN STATE, NIGERIA: POLICY RECOMMENDATIONS FOR SMALL-SCALE FOOD BUSINESS DEVELOPMENT - Ajibade, Iyanuoluwa; Alabi, Dorcas (Applied Studies in Agribusiness and Commerce, 2026)
Locally produced drinks play a significant role in the cultural, economic and culinary lives of rural dwellers in Nigeria. However, factors influencing their consumption remain poorly understood. This study investigated these critical factors among local drink consumers in rural areas of Osun State, Nigeria with a view to suggesting policy recommendations for the development of small-scale local food business. It employed a multistage sampling procedure to select 205 respondents. Primary data collected with a structured interview schedule and in-depth interview guide were analysed using descriptive statistics and factor analysis. The study revealed that many (52.1% and 83.0%%) of the respondents were male and married, respectively, mean age was 40±12 years while mean household size was 6 persons. Zobo (100%), palm wine (99.5%), and soymilk (95.6%) were the most available local drinks in the study area. The sensory characteristics (63.45%), production (66.96%), and functional characteristics (74.03%) of the drinks were mostly considered by the consumers. The factors influencing consumption were the characteristics of the drinks, the educational background, and the economic status of the consumers. The study concluded that the identified factors were essential to the development of the local drinks industry and the small-scale food business in the study area. Policy recommendations that could provide a framework for this development were suggested based on the findings of the study.